Reduced breath condensate pH in asymptomatic children with prior wheezing as a risk factor for asthma - von Jagwitz, Marie; Pessler, Frank; Akmatov, Manas; Li, Jialiang; Range, Ursula; Vogelberg, Christian (Journal of allergy and clinical immunology, 2011)
Early noninvasive detection of increased risk of asthma with exhaled breath condensate (EBC) pH measurement has not been applied to preschool children. We sought to evaluate the ability of EBC pH measurement to identify young asymptomatic children at risk of asthma using the combination of recurrent wheezing and atopic sensitization as a proxy for a high risk of asthma. pH values were measured in deaerated EBC from 191 children (median age, 4.4 years [interquartile range, 2.2 years]). Children were divided into one of 5 groups: asymptomatic children with recurrent wheezy bronchitis with (group 1, n = 34) or without (group 2, n = 64) allergic sensitization, acute wheezy bronchitis (group 3, n = 18), allergic rhinoconjunctivitis without recurrent wheezy bronchitis (group 4, n = 15), and healthy control subjects (group 5, n = 60). The Asthma Predictive Index score was calculated for groups 1 and 2. Statistical significance was evaluated with the appropriate nonparametric tests, and the discriminatory accuracy was evaluated with receiver operating characteristic analysis. Deaerated EBC pH values were significantly lower in groups 1 and 3 than in groups 2, 4, and 5 (median, 7.49 [interquartile range, 0.94] and 7.44 [interquartile range, 0.70] vs 7.93 [interquartile range, 0.23], 8.02 [interquartile range, 0.17], and 7.96 [interquartile range, 0.25], respectively; P < .001 and area under the receiver operating characteristic curve ≥0.80 in all comparisons). The area under the curve for the differentiation between groups 1 and 2 improved from 0.80 to 0.94 (sensitivity, 0.94; specificity, 0.84; positive predictive value, 0.76) when breath condensate pH values and Asthma Predictive Index scores were combined. A reduced deaerated EBC pH value might help identify young asymptomatic children at high risk of asthma.